Leite A2A2: uma análise abrangente sobre seu surgimento, propriedades, mercado e evolução científica através da análise bibliométrica - Ferreira, Krízia Emanuelle dos Santos; Moura, Rafaela Ribeiro (Universidade Federal de São Carlos, 2024)
The ingestion of milk since childhood is emphasized as a fundamental part of human daily diet, occupying the first place as the most consumed food in the world. Considered a raw material of great nutritional and economic importance, milk consumption promotes food security and serves as a significant source of income for various rural producers. Currently, there has been discussion about the main impacts on human health associated with the consumption of bovine milk containing the A1 variant of β-casein. The differentiation between A1 and A2 β-casein, marked by the amino acid at position 67 (histidine in A1 and proline in A2), results in distinct products: "A1 milk" with homozygosity and heterozygosity, and "A2 milk" exclusively with homozygosity. The metabolism of the A1 variant synthesizes β-casomorphin-7 (BCM-7), affecting gastrointestinal motility as well as gastric and pancreatic secretions. In contrast, A2 β-casein, with proline at position 67, prevents or minimizes the release of the opioid BCM-7, resulting in the alternative peptide β-casomorphin-9. The hypothesis that the A1 variant may have adverse effects on health, related to the production of BCM-7 during digestion, raises concerns about heart diseases, diabetes, neurological disorders, among others. The interest in the A2 variant and its products has sparked significant debates and research, reflected in a comprehensive bibliographic analysis. Using the Web of Science database, this study provides an overview of the current state of research, identifying institutions, researchers, and trends. This research mapped articles published annually, the predominant directions in thematic content, frequently used citations, and prominent countries. The results highlight the urgency of making efforts to fully understand the possible ramifications of this innovative product for both human health and the dairy market in general.
A2A2 Milk: a comprehensive analysis of its emergence, properties, market and scientific evolution through bibliometric analysis
Keywords: β-caseína A2; Peptídeo opioide; Análise bibliométrica; Leite A2A2; β-casein A2; Opioid peptide; Bibliometric analysis; A2A2 milk; CIENCIAS AGRARIAS::CIENCIA E TECNOLOGIA DE ALIMENTOS::CIENCIA DE ALIMENTOS; CIENCIAS AGRARIAS::CIENCIA E TECNOLOGIA DE ALIMENTOS::TECNOLOGIA DE ALIMENTOS